Biodiversity and Seasonal Succession of Macrobenthos in Saltmarsh Habitat Adjacent to a Ship-Breaking Area - M. Shafiqul Islam; Hossain Zamal; Muhammad Shah Alam; Md. Maheen Mahmud Bappy; Abu Hena Mustafa Kamal; M. Belal Hossain; Takaomi Arai (Diversity)
The Fauzderhat coast of Chattogram (Bangladesh) is increasingly affected anthropogenic pressures, necessitating an understanding of its ecological conditions to inform effective ecosystem management. Despite this urgency, the local succession patterns and environmental impacts on macrobenthic communities remain poorly understood. This study examines the saltmarsh bed macrobenthos in Fauzderhat, documenting 81,724 individuals from 54 species. These include ten families and twenty-two species of annelids, ten and twelve species of arthropods, and ten and eleven species of mollusks, as well as six and nine species from different phyla. Seasonality showed significantly different patterns of changes, with the number of species and abundance peaking during the monsoon (53 species) and post-monsoon (21,969) conditions, respectively, and being lowest in the post-monsoon condition (39 species) and winter (18,265 individuals). Species richness, diversity, and evenness were significantly higher in monsoon and lower in post-monsoon conditions, with the differences being only significant in the former. Cluster analysis and line graphs indicated that average species abundance was lowest post-monsoon, increased through the winter and pre-monsoon conditions, then declined again during monsoon conditions. SIMPER analysis revealed the highest dissimilarity between pre-monsoon and post-monsoon conditions while winter and post-monsoon conditions showed the lowest dissimilarity of microbenthic assemblages. Correlation coefficients showed the macrobenthos were positively correlated with soil salinity, dissolved oxygen, and pH, while they were negatively correlated with sand, Inundation Period, and nutrients. CCA showed that monsoon conditions (higher water temperature, inundation period, and tidal height) created unfavorable environments for most species, except for several species. Conversely, winter favored species like M. oligobranchia. Post-monsoon nutrient levels increased stress, reducing species presence, while pre-monsoon conditions supported balanced diversity.